Mustelid and viverrid remains from the Pleistocene site of Cooper’s D, Gauteng, South Africa - O'Regan, Hannah J.; Cohen, Brigette F.; Steininger, Christine M. (My University, 2013)
Fossil mustelids and viverrids are rare in the African Pleistocene fossil record. The careful examination of sieved sediments from the well-dated Cooper’s D locality in Gauteng has revealed six new mustelid and viverrid specimens. These represent three uncommon genera – two mustelids, Propoecilogale bolti and Mellivora capensis, and a viverrid, Civettictis cf. civetta. We describe and figure these six specimens here. Cooper’sD is only the fourth African locality at which P. bolti has been identified, and it is the first of the Witwatersrand sites to contain remains of the African civet.
Keywords: Civettictis; Mellivora; Propoecilogale; civet; honey badger; weasel